Productivity and Nutrient Balance of an Intensive Rice–Rice Cropping System Are Influenced by Different Nutrient Management in the Red and Lateritic Belt of West Bengal, India - Shankar, Tanmoy; Malik, Ganesh Chandra; Banerjee, Mahua; Dutta, Sudarshan; Maitra, Sagar; Praharaj, Subhashisa; Sairam, Masina; Kumar, Duvvada Sarath; Dessoky, Eldessoky S.; Hassan, Mohamed M.; Ismail, Ismail A.; Saif, Tarek; et al. (Plants (Basel), 2021)
Rice is the lifeline for more than half of the world population, and in India, in view of its huge demand in the country, farmers adopt a rice–rice cropping system where the irrigation facility is available. As rice is a nutrient-exhausting crop, sustainable productivity of rice–rice cropping system greatly depends on appropriate nutrient management in accordance with the inherent soil fertility. The application of an ample dose of fertilizer is the key factor for maintaining sustainable rice yields and nutrient balance of the soil. Considering the above facts, an experiment was conducted on nutrient management in a rice–rice cropping system at the university farm of Visva-Bharati, situated in a sub-tropical climate under the red and lateritic belt of the western part of West Bengal, India, during two consecutive years (2014–2016). The experiment was laid out in a Randomized Completely Block Design with 12 treatments and three replications, with different rates of N:P:K:Zn:S application in both of the growing seasons, namely, kharif and Boro. The recommended (ample) dose of nutrients was 80:40:40:25:20 and 120:60:60:25:20 kg ha−1 of N:P2O5:K2O:Zn:S in the Kharif and Boro season, respectively. A high yielding variety, named MTU 7029, and a hybrid, Arize 6444 GOLD, were taken in the Kharif and Boro seasons, respectively. The results clearly indicated that the application of a recommended dose of nutrients showed its superiority over the control (no fertilizer application) in the expression of growth characters, yield attributes, yields, and nutrient uptake of Kharif as well as Boro rice. Out of the all treatments, the best result was found in the treatment where the ample dose of nutrients was applied, resulting in maximum grain yield in both the Kharif (5.6 t ha−1) and Boro (6.6 t ha−1) season. The corresponding yield attributes for the same treatment in the Kharif (panicles m−2: 247.9; grains panicle−1: 132.0; spikelets panicle−1: 149.6; test weight: 23.8 g; and panicle length: 30.6 cm) and Boro (panicles m−2: 281.6; grains panicle−1: 142.7; spikelets panicle−1: 157.2; test weight: 24.8 g; and panicle length: 32.8 cm) season explained the maximum yield in this treatment. Further, a reduction or omission of individual nutrients adversely impacted on the above traits and resulted in a negative balance of the respective nutrients. The study concluded that the application of a recommended dose of nutrients was essential for proper nutrient balance and sustainable yields in the rice–rice cropping system.